(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2024)
My article talks about the analysis of the Uzbek tribes of Shaybani Khan who moved to Central Asia during the 16th century and their influence on cultural, political and social issues in the country.